Regionalism and multilateralism politics, economics, culture - Meyer, Thomas 1943-; Sales Marques, Jose Luis de; Telò, Mario 1950-2023 (Routledge, 2019)
"This book discusses the impact of cultural diversities and identities on regional and interregional cooperation, as well as on multilateralism. Employing a comparative approach to organizations such as ASEAN, MERCOSUR, SAARC, and the African and European Unions, this volume seeks to understand their distinctive features and patterns of interaction. It also explores the diffusion of multidimensional interregional relations, including but not limited to the field of trade. Scholars from several disciplines and four continents offer insights concerning the consequences of both multiple modernities and the rise of authoritarian populism for regionalism, inter-regionalism, and multilateralism. Among alternative possible scenarios for global governance, the "new multilateralism" receives special attention. This book will be of key interest to European/EU studies, economics, history, cultural studies, international relations, international political economy, security studies, and international law"--
Description based on online resource; title from digital title page (viewed on July 14, 2020)
Keywords: Regionalism; International cooperation